1998
DOI: 10.1021/ja980146m
|View full text |Cite
|
Sign up to set email alerts
|

Migration Reaction of a Hypervalent Fragment: Base-Induced Migration of a Phosphorane Fragment from Iron to the Cyclopentadienyl Ring in Cp(CO)2Fe{P(OC6H4Y)(OC6H4Z)} (Y, Z = NMe, NH, O)

Abstract: Iron phosphorane complexes, (Y, Z = NMe, O), react with lithium diisopropylamide (LDA) and then MeI to give showing the first example of migration of a hypervalent phosphorus fragment. The structure of one of the migration products, was determined by X-ray analysis. Spectroscopic monitoring of the migration reaction suggests that the reaction is initiated by a proton abstraction on the Cp ring by LDA, followed by migration of the phosphorane fragment to the Cp ring to give which is converted into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 40 publications
3
6
0
Order By: Relevance
“…Therefore, Berry pseudorotation may be slower for complexes 2 , if it occurs at all, whereas it does occur faster for 4 than the NMR time scale. This tendency is the same as that exhibited by the corresponding iron complexes …”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Therefore, Berry pseudorotation may be slower for complexes 2 , if it occurs at all, whereas it does occur faster for 4 than the NMR time scale. This tendency is the same as that exhibited by the corresponding iron complexes …”
Section: Resultssupporting
confidence: 77%
“…(iv) In the IR spectrum, two absorption bands due to ν CO are observed at 2020 and 1959 cm -1 . These spectroscopic features are very similar to those for the corresponding iron complex …”
Section: Resultssupporting
confidence: 73%
“…5 , Scheme 4 ). Hypervalent P(III)–O interactions with similar P–O distances are documented for five membered rings [ 47 48 ] as well as for acyclic systems [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reaction of the in situ generated anion 194a Moreover, it was found that in the presence of a base a migration of pentacoordinate phosphorane fragment occured from the transition metal in 196 to the carbon atom in the Cp ring in 201 [129] (Scheme 73). Moreover, it was found that in the presence of a base a migration of pentacoordinate phosphorane fragment occured from the transition metal in 196 to the carbon atom in the Cp ring in 201 [129] (Scheme 73). Moreover, it was found that in the presence of a base a migration of pentacoordinate phosphorane fragment occured from the transition metal in 196 to the carbon atom in the Cp ring in 201 [129] (Scheme 73).…”
Section: Scheme 71 Preparation Of Chiral Metallophosphoranes 192mentioning
confidence: 99%